PARTICLES THAT AFFECT THE SUBJECT IN ARABIC (Inna and Its Sisters إنَّ وأخَواتُها ) (Eureka Journal of Language, Culture & Social Change, 2026)
In the literature and sources on Arabic linguistics, the issue of the accusative case of nouns and its expression through particles is discussed in a scattered manner and, in some works, only very briefly. The purpose of this study is to identify and analyze the semantic characteristics and syntactic functions of particles belonging to the class of function words that affect the subject of a nominal sentence in Modern Standard Arabic.
Keywords: nominal sentence (الجملة الإسمية ), subject (المبتدأ ), predicate (الخبر ), accusative case ( المنصو ب ), particles ( الحرو ف ).